MOTIVASI DAN KOMPETENSI SUMBER DAYA MANUSIA PADA KINERJA GURU TAMAN KANAK-KANAK - Widyaratna, Lianita; Dedi Sukariyono; Kristina Fatmawati (Bajang Institute, 2024)
This research aims to determine the influence of motivation and human resource competence on the performance of kindergarten teachers in part or together. The population in this study were kindergarten teachers in Beji District, Pasuruan Regency. The sampling technique uses non-probability sampling with random sampling techniques. The sample used in this research was 84 respondents using the Slovin formula. The method used in this research was a quantitative research approach. This research uses multiple linear regression analysis with data collection using a questionnaire with a Likert scale. The results of research partially using the t test show that motivation and human resource competence influence teacher performance. For research results, simultaneously or together, motivation and HR competency also influence teacher performance in Beji District, Pasuruan Regency by 35.3%.